CONTRIBUTION OF GENDER PSYCHOLOGY TO THE DEVELOPMENT OF THE MODERN EDUCATIONAL SYSTEM - Ioffe, E.V. (Modern Psychology, 2019)
This paper presents the theoretical and practical implications of the development of special online training course “Current problems of gender psychology in education”. The course meets the challenges, which orient teachers to modern communicate, free from gender stereotypes, to create conditions for the realization of the needs and interests of all pupils, regardless of gender. The course offers a study of new topics, considering the latest scientific developments in the field of gender psychology, which are of particular importance to education. The specificity of gender  socialization in various educational institutions; gender stereotypes of teachers about the educational and professional preferences of children and youngsters of both sexes; peculiarities of teachers' attitude towards gender-non-conformal children; gender problems in homogeneous groups; development of gender competence of teachers are considered.
Keywords: gender relations, gender socialization, gender competence, gender stereotypes.; gender relations; gender socialization; gender competence; gender stereotypes